Packaged food safety in urban area : an observation from the Malaysian law of tort on negligence - Razman, Muhammad Rizal; Ramli, Nor Azam; Azlan, Azrina; Che Ngah, Mohamad Suhaily Yusri (WFL Publisher, 2013)
The law of tort on negligence plays an important role in protecting individual from contaminated food. The use of the law of negligence in the area of an individual protection is largely in reply to the necessity of each individual to protect his rights and interests in consuming food, including packaged food. Therefore, the aim of this paper was to examine the use of the law of tort on negligence in relation to the individual protection on the packaged food safety in urban area from Malaysian legal perspectives, identify actions and cases which deal with individual protection on contaminated packaged food from the Malaysian legal perspectives and lastly, discuss the law of tort on negligence as a means to protect individuals from contaminated packaged food in Malaysia in order to achieve sustainable development.